Mechanical thrombectomy in deep venous thrombosis: Single center experience - Mesut Özgökçe; Suat İnce; Hüseyin Akdeniz; Ensar Türko; Saim Türkoğlu; Şahin Şahinalp; Zakir Sakcı (Van Tıp Dergisi, 2020)
INTRODUCTION: Deep venous thrombosis(DVT) is the coagulum formation due to stasis,endothelial damage and hypercoagulability,which is also called as Virchow triad.It may cause severe sequel and death if it is not treated in a timely manner.In this article,we aimed to share the factors that affect the success rate of DVT patients treated with mechanical thrombectomy and our experience on this subject. METHODS: In the last year,mechanical and aspiration thrombectomy was performed in 13 patients with lower extremity venous thrombosis in the acute and subacute period in the interventional radiology clinic. RESULTS: Sonographically 3 patients were acute and 10 patients were subacute DVT.In the case of acute DVT,mechanical aspiration led to significant lumenal opening.In subacute DVT patients,partial opening with mechanical thrombectomy was achieved while half as much lumenal opening was provided as a result of simultaneous aspiration thrombectomy.In a month later,no significant luminal openings were observed in the subacute period when complete opening was observed in the acute phase. DISCUSSION AND CONCLUSION: We do not have enough information about what causes the long-term results of thrombectomy because it is a procedure that has recently been put into practice.However,because it reduces the thrombus burden and improves the efficacy of medical treatment,it is thought that the vein reduces the possibility of recurrent thrombosis and gives positive results in the long term.If the procedure is done in the early period with vena cava filtration,it is a safe and effective treatment method.Mechanical thrombectomy alone should not be sufficient and should be supported by aspiration,especially in long-standing cases from fifteen days.